IDENTIFIKASI MORFOLOGI DAN KEANEKARAGAMAN KEPITING PADA TIMBUNAN BERBATU DI PANTAI PESISIR MALALAYANG DUA KOTA MANADO - Fatmawati Amin; Darus Saadah J Paransa; Medy Ompi; Desy M.H. Mantiri; Farnis Bineada Boneka; Ockstan Kalesaran (JURNAL PESISIR DAN LAUT TROPIS, 2021)
The diversity of crabs in the Malalayang One coast is thought to vary between research locations and limited information on biota that live on rocky, sandy and muddy coastal beaches. Sampling was carried out at low tide at night by capturing directly using a protected hand and for lighting with the help of a flashlight. The collected samples were taken to the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Sciences, UNSRAT to be identified and for diversity using the Shanon-winer mathematical formula. The results of crabs obtained at five coastal locations on the coast of Malalayang, Manado, with a total of 106 with 7 species, namely Metopograpsus latifrons, Sesarmops impressus, Ocypode kuhlii, Macrophthalmus mareotis depressus, Uca vocans dussumieri, Grapsus Longitarsis and Grapsus albolineatus.Keywords: Crab, Morphology, Diversity, Coastal Ecosystem.